2014
DOI: 10.1002/jcp.24525
|View full text |Cite
|
Sign up to set email alerts
|

BMP-2 Induction of Dlx3 Expression Is Mediated by p38/Smad5 Signaling Pathway in Osteoblastic MC3T3-E1 Cells

Abstract: Dlx3 is essential for osteoblast differentiation and bone formation, and its expression is regulated by bone morphogenetic protein-2 (BMP-2). However, the intimate mechanism of BMP-2 regulation of Dlx3 transcription in osteoblasts is still unknown. Considering the important roles of Smad5 and p38 in osteoblast differentiation, we hypothesized that Smad5 and p38 mediated BMP-2-induced Dlx3 transcription in osteoblasts. We found activation of Smad5 and p38 increased the expression of Dlx3, whereas knocking down … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(16 citation statements)
references
References 55 publications
0
15
0
1
Order By: Relevance
“…5, 21 Thus, we investigated whether KDM5A inhibits BMP2-induced osteoblastic differentiation through altering the BMP2-SMAD1/5/8 pathway in the KDM5A overexpressed MSCs. The results showed that phosphorylated SMAD1/5/8 was obviously increased after BMP2 treatment for 4 h in normal MSCs, which were not significantly changed by KDM5A overexpression (Figure 5a).…”
Section: Resultsmentioning
confidence: 99%
“…5, 21 Thus, we investigated whether KDM5A inhibits BMP2-induced osteoblastic differentiation through altering the BMP2-SMAD1/5/8 pathway in the KDM5A overexpressed MSCs. The results showed that phosphorylated SMAD1/5/8 was obviously increased after BMP2 treatment for 4 h in normal MSCs, which were not significantly changed by KDM5A overexpression (Figure 5a).…”
Section: Resultsmentioning
confidence: 99%
“…In short, Osteoblasts and osteoblastic lineage cells modulate the formation and activity of osteoclasts by expressing RANKL and OPG, which induce and inhibit osteoclastogenesis, respectively ( Krum et al, 2010 ). On the other hand, BMPs, belong to the transforming growth factor β (TGF-β) superfamily, which have been identified as inducers of ectopic bone and cartilage formation ( Yang et al, 2014 ). BMP2 is one of the most important cytokines playing important roles in bone development and fracture repair ( Jang et al, 2012 ).…”
Section: Discussionmentioning
confidence: 99%
“…Another DLX member, Dlx3 , is also induced by BMP-2. In this case, it occurs through cooperation between SMAD5 and pp38 as they translocate to the nucleus and exert their function on the Dlx3 promoter (Yang et al, 2014 ). These p38-activated osteogenic events continue with the phosphorylation of Osterix at serines Ser77 and Ser33.…”
Section: The Study Of P38 In Bone: Different Strategies the Same Goamentioning
confidence: 99%